Récits d´insertion de jeunes et régimes de temporalité - Didier Demazière; Claude Dubar (Temporalités)
The authors return to their recently republished analysis of a body of interviews with young people talking about their professional insertion in France in the early 1990s  (Analyser les entretiens biographiques, Presses de Laval, 2004). They question those interviews afresh from the point of view of the temporalities that intervene in the four types of discourse underlying the narratives. Taking off from the concept of historic forms found in the epistemology of history (Kosselleck, Hartog..), they distinguish four regimens of temporality according to the way the young people relate to the past, the present and the future. The utopian regimen is eschatological for those who dissociate themselves totally from a past of suffering and hope to be saved by some powerful Other(s). The passeistic (backward looking) regimen appears in dreams of an independent small business, of a craft or job typical of the male occupations of yesteryear. The futuristic regimen belongs to the most privileged youths who describe their project and the different steps needed to make it come true. The present regimen is that of young women locked into their positions as non-specialized employees or mothers tied to their domestic roles, with no particular career to look forward to.